Multimodal fluorescently labeled polymer-coated GdF3 nanoparticles inhibit degranulation in mast cells - Shapoval, Oleksandr; Sulimenko, Vadym; Klebanovych, Anastasiya; Rabyk, Mariia; Shapoval, Pavlo; Kaman, Ondřej; Rydvalová, Eliška; Filipová, Marcela; Dráberová, Eduarda; Dráber, Pavel; Horák, Daniel (Nanoscale, 2021)
Multimodal gadolinium fluoride nanoparticles belong to potential contrast agents useful for bimodal optical fluorescence and magnetic resonance imaging. However, the metallic nature of the nanoparticles, similarly to some paramagnetic iron oxides, might induce allergic and anaphylactic reactions in patients after administration. A reduction of these adverse side effects is a priority for the safe application of the nanoparticles. Herein, we prepared paramagnetic poly(4-styrenesulfonic acid-co-maleic acid) (PSSMA)-stabilized GdF3 nanoparticles with surface modified by Atto 488-labeled poly(styrene-grad-2-dimethylaminoethyl acrylate)-block-poly(2-dimethylaminoethyl acrylate) (PSDA-A488) with reactive amino groups for introduction of an additional imaging (luminescence) modality and possible targeting of anticancer drugs. The saturation magnetization of GdF3@PSSMA particles according to SQUID magnetometry reached 157 Am2 kg-1 at 2 K and magnetic field of 7 T. GdF3@PSSMA-PSDA-A488 nanoparticles were well tolerated by human cervical adenocarcinoma (HeLa), mouse bone marrow-derived mast cells (BMMC), and rat basophilic mast cells (RBL-2H3); the particles also affected cell morphology and protein tyrosine phosphorylation in mast cells. Moreover, the nanoparticles interfered with the activation of mast cells by multivalent antigens and inhibited calcium mobilization and cell degranulation. These findings show that the new multimodal GdF3-based nanoparticles possess properties useful for various imaging methods and might minimize mast cell degranulation incurred after future nanoparticle diagnostic administration.
Keywords: Growth Differentiation Factor 3; Mice; polymery; Rats; mastocyty; Mast Cells; Nanoparticles; Polymers; Animals; růstový diferenciační faktor 3; krysa rodu Rattus; Humans; lidé; zvířata; degranulace buněk; myši; Cell Degranulation; nanočástice